Terpaan Media Sosial Tiktok Terhadap Tingkat Partisipasi Politik Mahasiswa Pada Pemilihan Presiden Indonesia Tahun 2024 - Sari, Wina Puspita; Putriana, Muria; Bachtera, Rifki Azizan; Firdaus, Muhammad Reza; Wihadi, Afriza; Reyfaldi, Rananda Adrian; Pamungkas, Bintang Fajar; Sadewo, Rio (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study aims to analyze the various aspects of exposure that occur, including the types of content presented, interactions between users, and their political impact. The research method used is quantitative by using strata sampling techniques to structure the population so as to provide greater sampling efficiency. This research aims to provide a comprehensive understanding as well as the effects of TikTok social media exposure on political participation in the 2024 Presidential election, as well as its consequences in a broader political context. The results of this study are expected to help develop knowledge about public relations strategies in their implementation on social media and serve as a foundation for the development of more effective political communication strategies in the future.